Mosquito pica a gente - Pereira, Angela Aparecida Beraldo; Feijó, Giane Felix; Ribeiro, Onevan da Silva; Bordinhão, Andréia Jonceline Chiozini; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf